Implementasi Fungsi Uang Pada Sistem Perekonomian Dalam Novel Negeri Para Bedebah Karya Tere Liye - Rahayu Indah Anggraeni; Dini Astri Wijayanti; Eva Dwi Kurniawan (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to describe the function of money in the world economy using the novel Negeri Para Bedebah by Tere Liye. The research method used in studying the novel Negeri Para Bedebah is a qualitative descriptive method, this method contains quotes from the novel which can provide an overview of the presentation of research results. The theory used in this research is based on the Function of Money theory (Gilarso: 2004). The object of this research is the function of money in the world economy in the novel Negeri Para Bedebah by Tere Liye. The results of the research show that there are 5 functions of money, namely money as a means of exchange (means of payment), money as a unit of account or measure of value (account unit), money as a means of payment (means of payment), money as a means of storing wealth (store of value), money as a driver of economic activity.